KEBIJAKAN LUAR NEGERI NAJIB RAZAK TERHADAP KONSOLIDASI THAILAND DAN GERAKAN ALIANSI SEPARATISME ETNIS MELAYU DI THAILAND SELATAN DI TAHUN 2013-2016 - Hardi Alunaza SD , Retno Riyanti Sastro Amijoyo (Mandala: Jurnal Ilmu Hubungan Internasional, 2019)
This paper aims to discuss Malaysian foreign policy in influencing the movement of separatism in Southern Thailand by the ethnic Malay alliance. The dynamics of separatism in Southern Thailand is the result of a process of conflict between religious groups and the harmonious relations between the majority and minorities. In this conflict, Malaysia is a facilitator, seen from various visits and efforts taken by Malaysia to create peace in the region of Thailand. This paper will focus on several matters related to how rational actors influence the movement of separatist movements in Southern Thailand and how the prospects for peace and consolidation after a meeting between the Thai government and consultants representing the alliance of separatism. The method of this paper uses descriptive methods with a qualitative approach in analyzing the phenomema. The technique of collecting data is done through various literature, journals, articles, and reading materials that are related to the issues to be discussed. This paper will be focused on two political angles, namely; (1) Direction of Najib Razak's foreign policy in 2013 (2) Direction of foreign policy for Najib Razak in 2016. The result of the discussion of this paper is through the government of Najib Razak, Malaysia consolidates Thailand with steps to resolve conflict namely peacemaking (reconciliation) and peacebuilding (social reconstruction).